Ethnic studies and multiculturalism - La Belle, Thomas J. (SUNY series, frontiers in education., 1996)
La Belle and Ward address a major question confronting American higher education - How do colleges and universities best prepare students for common citizenship in a diverse, democratic state while also nurturing their groups' cultures, values, and institutional participation? The authors clarify current debates about diversity and the content of curriculum, what one commentator calls the "culture wars." The book includes an overview of ethnicity, intergroup relations,